2019
DOI: 10.1088/1748-9326/ab4cd8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the trends of vegetation net primary productivity in China between 1982 and 2015

Abstract: China has been experiencing significant climate and land use changes over the past decades. The way in which these changes, particularly a warming hiatus and national ecological restoration projects that occurred almost concurrently in the late 1990s, have influenced vegetation net primary productivity (NPP), is not well documented. Here, we estimated annual and seasonal changes in China's NPP between 1982 and 2015 using the Carnegie-Ames-Stanford Approach model and examined their shifting years (SHYs) caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 49 publications
(51 reference statements)
1
25
0
Order By: Relevance
“…This dataset was derived from a widely used Moderate Resolution Imaging Spectroradiometer (MODIS) product, and was calculated using the C5 MOD17 algorithm with data validation from flux towers (Zhao et al 2005; Zhao & Running 2010). For comparison, we obtained a flux‐based GPP dataset (Yao et al 2018) from 1982 to 2015 estimated with the Model Tree Ensemble algorithm at 0.1° resolution and an improved NPP dataset (Feng et al 2019) from 1982 to 2015 estimated with the Carnegie‐Ames‐Stanford Approach (CASA) at 8‐km resolution. We also obtained biomass‐estimated NPP data for 1099 forest stands in China from a recent publication (Michaletz et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…This dataset was derived from a widely used Moderate Resolution Imaging Spectroradiometer (MODIS) product, and was calculated using the C5 MOD17 algorithm with data validation from flux towers (Zhao et al 2005; Zhao & Running 2010). For comparison, we obtained a flux‐based GPP dataset (Yao et al 2018) from 1982 to 2015 estimated with the Model Tree Ensemble algorithm at 0.1° resolution and an improved NPP dataset (Feng et al 2019) from 1982 to 2015 estimated with the Carnegie‐Ames‐Stanford Approach (CASA) at 8‐km resolution. We also obtained biomass‐estimated NPP data for 1099 forest stands in China from a recent publication (Michaletz et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Normally, linear regression is used to analyze the changing trend of a time series. However, previous studies have indicated that ordinary linear regression models cannot describe long-term vegetation changes due to climate change and human activities [30][31][32]. In this study, some linear regression models were transformed into piecewise regression models according to the Akaike information criterion (AIC).…”
Section: Piecewise Regression Analysismentioning
confidence: 99%
“…Taking the annual cumulative precipitation, the annual average air temperature, the annual cumulative sunshine duration, and the proportion of vegetation as input data, the multiple linear regression model can simulate NPP change [30]. We built a multiple linear regression model like Equation (2):…”
Section: Contribution Of Variables Based On Multiple Regression Modelmentioning
confidence: 99%
“…Relatively abundant studies have focused on the impacts of temperature and precipitation changes on greening and browning using satellite measured normalized difference vegetation index (NDVI) or enhanced vegetation index (EVI) (Sarmah et al 2018;Du et al 2019;Feng et al 2019b;Liu et al 2019;Qian et al 2019;Sun et al 2019;Wang et al 2019;Li et al 2020a;Parida et al 2020;Yuan et al 2020). Studies using other indicators of vegetation are relatively limited and some of them are mentioned here, e.g., LAI (Piao et al 2015;Chen et al 2019), foliar projective coverage (FPC, Cuo et al 2016), tree ring (Shi et al 2019), ecosystem indices (Fu et al 2019), simulated NPP (Zhuang et al 2010;Piao et al 2012;Bao et al 2019;Feng et al 2019b), modeled carbon and water use efficiency (El Masri et al 2019), and observed or surveyed phenological states and NPP (Niu et al 2019;Li et al 2020b). Few have studied the effects of cloud cover and CO 2 changes (Piao et al 2012;Cuo et al 2016) on vegetation.…”
Section: Introductionmentioning
confidence: 99%